Optimising transcranial direct current stimulation application for the enhancement of exercise performance: a review - Lewis, Aidan; Rattray, Ben; Flood, Andrew (Frontiers in Physiology, 2025)
Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation technique that has shown potential in enhancing performance across a range of exercise types. However, the variability in its effectiveness suggests that outcomes may be contingent on how stimulation is applied. This review evaluates the current evidence surrounding the optimisation of tDCS for performance enhancement, focusing on individual stimulation parameters; timing, intensity, current density, montage, and electrode configuration, and their interactions. We highlight how modifications in these dose components can produce non-linear and sometimes paradoxical effects on corticospinal excitability, the primary mechanistic rationale proposed for tDCS-related performance gains. Evidence suggests that online vs offline stimulation, session duration, dual-dosing protocols, and extracephalic or high-definition montages can all substantially influence psychophysiological outcomes, though findings remain inconsistent. Through the review, we identify significant gaps in comparative data and cautions against assumptions that increased stimulation intensity or duration equates to improved performance. We critique the reliance on outdated methodologies including the use the 10–20 EEG system, and conclude by providing practical recommendations for future research, calling for systematic investigations of dose interactions, protocol standardisation, and direct comparisons of novel and established tDCS methods. These steps are necessary to utilise tDCS to its full potential in the context of exercise performance.